Factors influencing Chinese female expatriates' performance in international assignments - Shen, Jie; Jiang, Fuming (Routledge, 2011)
The current literature is mixed regarding what factors determine expatriate performance. In this study, we developed and tested a model to examine the relationship among family problems, expatriate-efficacy, host-country nationals' (HCNs') prejudice against women, perceived organizational support (POS) and Chinese female expatriate performance in international assignments. Our results indicated that HCNs' prejudice against women had a significant negative relationship and expatriate-efficacy had a significant positive relationship with female expatriate performance. POS and family problems moderated the relationship between HCNs' prejudice against women and female expatriate performance. However, family problems were not significantly related to female expatriate performance. Implications for research and practice are discussed.